A Case Report On Primary Infertility And Diabetic Mellitus - Pratiksha Ramteke, Sarika Selsurkar, Roshan Umate (Drugs and Cell Therapies in Hematology, 2021)
Diabetes is known to influence both men and women’s fertility and reproductive health. Diabetes can affect hormones, causing implantation and/or pregnancy to be delayed or unsuccessful. Diabetes is also linked to poor sperm and embryo quality, as well as DNA damage (genetic mutations and deletions). Patient history: A 43 year old female was admitted in A.V.B.R.H. with chief complaint of Pain in abdominal, pre vaginal bleeding, and high glucose levels with elderly G1.p1 .D0 .A0 with 6 weeks and 6 days GA with IVF conceptions diabetes mellitus. Clinical finding: The patient had done all necessary investigations by physician order. Medical Management: After physical examination and investigation, doctor was detected a case of 6 week and 6 day diabetes mellitus with Patient was treated analgesic drugs to reduce pain. Also provide a calcium supplements and iron supplements present case was stable. According to ultrasonography finding. Nursing Management: Administration fluid replacement.i.e DNS and RL, monitor fetal heart rate and vital signs per hourly. Conclusion: Pregnancy conceived with in vitro fertilization increasing the more risk of diabetes mellitus,